Devonian–Mississippian magmatism related to extensional collapse in Svalbard: implications for radiating dyke swarms [version 1; peer review: 2 approved] - Gillian R. Foulger; Sebastian Tappe; Jean-Baptiste P. Koehl; Ingrid M. Anell (Open Research Europe)
Background Despite extensive studies of the Mesozoic–Cenozoic magmatic history of Svalbard, little has been done on the Paleozoic magmatism due to fewer available outcrops. Methods 2D seismic reflection data were used to study magmatic intrusions in the subsurface of eastern Svalbard. Results This work presents seismic evidence for west-dipping, Middle Devonian–Mississippian sills in eastern Spitsbergen, Svalbard. The sills crosscut a late Neoproterozoic Timanian thrust system, which was reworked during Caledonian contraction. The sills are unconformably overlain by relatively undeformed Pennsylvanian–Mesozoic sedimentary rocks and crosscut by Cretaceous dykes of the High Arctic Large Igneous Province. The sills probably intruded along extensional fractures during post-Caledonian reactivation–overprinting of the late Neoproterozoic thrust system. Kimberlitic accessory minerals in exposed contemporaneous intrusions and the chemical composition of chromium spinel grains in Upper Triassic sedimentary rocks in Svalbard suggest that the Middle Devonian–Mississippian intrusions in eastern Spitsbergen show affinities with diamond-rich kimberlites in northwestern Russia. Overall, the sills were emplaced during a regional episode of extension-related Devonian–Carboniferous magmatism in the Northern Hemisphere including the Kola–Dnieper and Yakutsk–Vilyui large igneous provinces. Conclusions This work presents the first evidence for extensive Middle Devonian–Mississippian magmatism in Svalbard. These intrusions may be part of the Kola–Dnieper Large Igneous Province and intruded parallel to preexisting, Proterozoic–early Paleozoic orogenic structures. Their strike is inconsistent with a source from a potential mantle plume center in the eastern Barents Sea. Thus, the radiating emplacement pattern of the magmatic intrusions of the Kola–Dnieper Large Igneous Province are not the product of plume-related uplift but of structural inheritance. A similar line of reasoning is successfully applied to intrusions of the Yakutsk–Vilyui and High Arctic large igneous provinces.